Gender equality in the Qur’an: An Analysis of surah an-Nisa’ verses 1 and 34 in the exegesis of al-Tabari and al-Rāzī - Ismail, Nurjannah; Firdaus, Muhammad; Darmawijaya, Edi (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
Surah An-Nisa' verses 1 and 34 have been central to discussions on gender. According to the interpretations of Imam al-Ṭabarī and Imam al-Rāzī, these verses place women in a subordinate role, both in domestic and non-domestic spheres. This interpretation is considered biased, not reflecting the true essence of the Qur'an. Therefore, further research is necessary to uncover the Qur'an’s intended view on gender in these verses. The study uses a descriptive-analytical method with a qualitative approach, gathering data from books, theses, and articles. The findings reveal that al-Ṭabarī and al-Rāzī's interpretations reinforce male superiority in patriarchal tradition, stating that Eve was created from Adam's rib and that the husband is the absolute leader of the wife. However, contemporary scholars argue that interpreting "nafs" as referring to the unity of humanity without any connotation of gender superiority, emphasizing equality in Islam. The Qur'an advocates for justice in gender issues, making traditional interpretations obsolete in today's context. Regarding Surah An-Nisa' verse 34, al-Ṭabarī and al-Rāzī interpreted men as the rightful leaders over their wives due to the advantages given by Allah, with financial responsibility as the foundation of their authority. However, modern-contemporary tafsir scholars reject this view, interpreting qiwāmah as shared responsibility regardless of gender, emphasizing partnership in the household and gender equality in Islam. This reflects efforts to understand Qur'anic verses contextually and inclusively, supporting the principles of equality and justice.